Simultaneous Determination of Halobetasol Propionate and Fusidic Acid Related Substances by Reversed Phase High Performance Liquid Chromatographic Method - Ankam, R.; Mukkanti, K.; Durgaprasad, S.; Naidu, P.V.L. (Asian Journal of Chemistry, 2010)
A simple fast, accurate, precise and cost effective isocratic RP-HPLC method is developed for simultaneous determination of halobetasol propionate and fusidic acid as well as its impurities in the cream formulation. The chromatography equipped with Zorbax SB phenyl (250 mm × 4.6 mm) column using a mobile phase of buffer (0.1 % triethylamine buffer pH adjusted to 2.0 with orthophosphoric acid) acetonitrile, methanol in the ratio of 40:35:25 v/v with a flow rate of 1.5 mL/min, with ultraviolet detector configured at 240 nm.